2023
DOI: 10.1037/edu0000762
|View full text |Cite
|
Sign up to set email alerts
|

Social perspective taking: A professional development induction to improve teacher–student relationships and student learning.

Abstract: When teachers struggle to understand students’ thoughts, feelings, and motivations, the teacher–student relationship typically suffers. Better social perspective taking—understanding the thoughts, feelings, and motivations of others—should facilitate these relationships. In this preregistered field experiment, teachers (N = 105) from a kindergarten-to-ninth-grade charter school network participated in a new social perspective-taking induction aimed at helping them better understand their most perplexing studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 91 publications
(162 reference statements)
0
3
0
Order By: Relevance
“…Additionally, this study suggests that teacher educators and administrators should continue to encourage teachers to build strong relationships with their students, differentiate instruction, and provide students with choice, as these practices provide a relational and pedagogical foundation for SVPs. A great deal of previous research has identified professional learning programs and supports that can help educators hone their relational skills ( Conner et al, 2023b ; Duong et al, 2019 ; Gehlbach et al, 2023 ; Kennedy & Haydon, 2021 ), their facility with differentiation ( De Neve & Devos, 2017; Smets et al, 2020 ), and their approach to autonomy support in the classroom ( Reeve et al, 2020 ). Furthermore, some research suggests that increasing teacher job satisfaction (e.g., Cheon et al, 2020 ), need satisfaction (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study suggests that teacher educators and administrators should continue to encourage teachers to build strong relationships with their students, differentiate instruction, and provide students with choice, as these practices provide a relational and pedagogical foundation for SVPs. A great deal of previous research has identified professional learning programs and supports that can help educators hone their relational skills ( Conner et al, 2023b ; Duong et al, 2019 ; Gehlbach et al, 2023 ; Kennedy & Haydon, 2021 ), their facility with differentiation ( De Neve & Devos, 2017; Smets et al, 2020 ), and their approach to autonomy support in the classroom ( Reeve et al, 2020 ). Furthermore, some research suggests that increasing teacher job satisfaction (e.g., Cheon et al, 2020 ), need satisfaction (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Learning which interventions are sticky enough to persist over time will be of particular interest. However, learning which interventions are so strong that targets detect differences in their interactions with perceivers may be an even more compelling outcome (e.g., Gehlbach et al, 2022).…”
Section: Improving Sptmentioning
confidence: 99%
“…Finally, as our literature review shows, our model builds from extensive wisdom accumulated from laboratory studies that signal how SPT can improve numerous outcomes. We complement these past efforts with a model focused on how SPT attempts may play out in real-world situations, bearing in mind that the extent to which knowledge from these studies generalizes to real-world interactions is ultimately an empirical question (Gehlbach et al, 2022).…”
Section: Introductionmentioning
confidence: 99%